Molecular mechanisms of biomass increase in plants. Issue 1 (January 2017) - Lima, Marcelo de Freitas; Eloy, Nubia Barbosa; Siqueira, João Antonio Batista de; Inzé, Dirk; Hemerly, Adriana Silva; Ferreira, Paulo Cavalcanti Gomes
Abstract: Biomass consumption continues to increase worldwide for the provision of human energy needs. These high pressures for energy will determine the demand for crop plants as a resource for biofuel, heat and electricity. Thus, the search for plant traits associated with genetic increases in yield is unconditional. Here, we propose exploiting recent advances in plant biomass enhancement in non-crop as well as in crop plants. For this purpose, biotechnological approaches that are well known rapid ways of enhancing the plant traits, as well as the traditional way of improving plants through plant breeding selecting for desirable phenotypes are excellent techniques to improve plant biomass and reduce the dependence on fossil fuels. Obviously, many genes can be associated with promising phenotypes however this review will focus on genes selected from different plant networks.